DNA repair genes in the Megavirales pangenome. (June 2016) - Blanc-Mathieu, Romain; Ogata, Hiroyuki
Highlights: Megavirales pangenome encodes key enzymes involved in five major DNA repair pathways. Larger Megavirales genomes tend to encode more genes for DNA repair enzymes than smaller Megavirales genomes in consistence with Drake's rule. This suggests that these enzymes play a crucial role in maintaining the integrity of their large genomes. A few DNA repair enzymes are inferred to be encoded in the last common ancestors of individual families in the order Megavirales, suggesting that they already had the potential to achieve a relatively large genome compared to extant DNA viruses lacking DNA repair genes. Individual families of Megavirales gradually increased their genome size by acquiring new repair functions from their hosts through horizontal gene transfer. Abstract : The order 'Megavirales' represents a group of eukaryotic viruses with a large genome encoding a few hundred up to two thousand five hundred genes. Several members of Megavirales possess genes involved in major DNA repair pathways. Some of these genes were likely inherited from an ancient virus world and some others were derived from the genomes of their hosts. Here we examine molecular phylogenies of key DNA repair enzymes in light of recent hypotheses on the origin of Megavirales, and propose that the last common ancestors of the individual families of the order Megavirales already possessed DNA repair functions to achieve and maintain a moderately large genome and that this repair capacity gradually increased, in a family-dependent manner, during their recent evolution.